Diretrizes para projetos habitacionais sustentáveis baseadas na categoria 1 do processo AQUA - Esmeraldo, Lara Barrocas Soares (2013)
To achieve a green building, special attention is required to the project stage once it will give the guidelines for the implementation, operation and maintenance of the building. Designers play a key role in the sustainable principles of the buildings, and the project must be oriented, since its beginning, to reach this goal. This can provide some changes to the entire production chain of the built environment. In Brazil, there is an inertia to the development of sustainable projects. Although there are professionals engaged in environmental movements, sustainable actions are just beginning. Thus, the incorporation of environmental demands to the design process became urgent. Thereby, this research proposes to investigate about the design of sustainable residential projects. The purpose of this research is to perform a study about the difficulties faced in the project process of certificated sustainable residential buildings, specifically with regards to the first category of the Technical Reference of the AQUA certification, which is the object of this study. In this context, this work seeks to identify how designers apply sustainable concepts in the project stage of residential green buildings, in order to implement a simplified methodology to facilitate its inclusion into the first category of the AQUA Process. The end result of this work will be the development of guidelines for the design of sustainable residential projects, based on the criteria from AQUA\'s first category. This will collaborate for a better understanding of this technical reference component and may also assist companies and designers who have not yet completed or started the certification process. Difficulties could be minimized and consequently the certification process of residential sustainable buildings projects will become easier.